Eco-friendly biofertilizer from rice straw waste - Lik Yang, Ooi; Fatin Arinah, Hanafi; Chin, Mei Lee (2021)
Rice straw is by product of rice plant produced after harvestation. 2,000,000 metric tonnes produced in each cultivation session in Malaysia With the complex lignocellulosic structure of the rice straw, rice straw does not degrade naturally. The problem comes when paddy farmers dispose the rice straw by burning it directly on the paddy field. This leads to serious air pollution and promotes the loss of nutrients from the soil. Degradation of rice straw by biofertilizer will be a good way to solve the problems.